2009
DOI: 10.1002/chp.20045
|View full text |Cite
|
Sign up to set email alerts
|

German ambulatory care physicians' perspectives on continuing medical education—A national survey

Abstract: Mandatory CME was accepted as a necessity already before the new legislation took effect, with prevailing skepticism at the same time. Future research is needed on how to motivate physicians and especially certain subgroups of physicians to use CME methods shown to be effective in changing clinical behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Thus the difference might have been in more extreme in a sample of purely conventional GPs. Nevertheless, other studies with different and partly representative samples of GPs sustain these results [5,7,15,25]. …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Thus the difference might have been in more extreme in a sample of purely conventional GPs. Nevertheless, other studies with different and partly representative samples of GPs sustain these results [5,7,15,25]. …”
Section: Discussionmentioning
confidence: 75%
“…interactivity, use of multiple methods, multimedia CME, case-based learning, and multiple exposures) have been shown to even change physicians behaviour [3,4]. Some previous studies have suggested the types of media preferred by general practitioners and hospital doctors specially in Germany for their learning activities, including aspects about new media [5-7]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies show differences between generalists and specialists in their participation in continuing medical education (CME) in different settings . Specialists in Latin America, for example, tend to have higher rates of attendance, participate more actively in discussions, and feel more comfortable sharing personal practice experiences with peers and faculty.…”
Section: Introductionmentioning
confidence: 99%
“…Kempkens et al examined opinions of CME by German ambulatory physicians. 17 Their findings indicate that physicians desire other parties (ie, insurance or government) to share financial responsibility for CME. Other CME concerns center on the relevance of the material and the seriousness of the session itself, in that participants were getting credits by paying for the sessions without attending most of them.…”
Section: Introductionmentioning
confidence: 99%
“…Other CME concerns center on the relevance of the material and the seriousness of the session itself, in that participants were getting credits by paying for the sessions without attending most of them. 17 Based on these documented concerns on the relevance, cost, and logistics of CME in various countries, this study examines the opinions of CME medical professionals in the United Arab Emirates. This is one of the first surveys to examine perspectives of CME in the United Arab Emirates, and seeks to expand knowledge surrounding CME and training in the Middle East.…”
Section: Introductionmentioning
confidence: 99%